The number of different types of dominating sets in binary trees - Oyewumi, Opeyemi (Stellenbosch : Stellenbosch University, 2025)
Oyewumi, Opeyemi. 2024. The number of different types of dominating sets in binary trees. Unpublished doctoral dissertation. Stellenbosch : Stellenbosch University [online]. Available: https://scholar.sun.ac.za/handle/10019.1/131880